AYURVEDA MANAGEMENT OF TRAUMATIC ARTHRITIS OF KNEE (JANU VATA) WITH SPECIAL REFERENCE TO ARJUNA KSHEERA PAKA- A CLINICAL STUDY - K, *Suguna; Rao, M.Paramkusha; Dixit, Renu (International Journal of Ayurveda and Pharma Research, 2016)
In this clinical study 40 Traumatic arthritis patients aged 35-65 years were selected at random in OPD of TTDs S.V Ayurvedic Hospital PG Dravyaguna Dept, Tirupati. In Group I, 20 patients were treated with Terminalia arjuna powder TAP (oral intake of Arjuna powder boiled with milk). In group II, 20 patients were treated with Terminalia arjuna Ksheerapaka powder TAKP (Arjuna powder boiled with milk and filtered into semisolid and made into fine powder). The aim of the study was comparative clinical evaluation between group I and group II in the management of Traumatic arthritis.Guggulu tablets are used for joint pains. But it has Lekhana and Medohara properties and causes Vata prakopa. Thats why there is an acute need for safe herbal drug. Therefore Arjuna, a Bhagna sandhanakara drug mentioned in Vrindamadhava is taken for the study. The form of drug is Arjuna bark powder by boiled with milk (Bhagna pibeth tvak payasarjunasya).It is observed that there is no significant difference between group I and group II in the mean values of fatigue, Pain radiating to other parts and walking time but significant difference were observed in ESR before and after treatment in group I and group II. Group II showed better results in reducing restricted movement and Group I shows better results in reducing inflammation.Based on all the observed results it can be concluded that Group II has showed highly significant improvement when compared in between groups, this may be due to Jeevaniya and Sandhaniya karma of milk which causes synergetic action of Arjuna karmas. No complications were observed in the clinical study.